What criteria are young people using to select mobile mental health applications? A nominal group study. (May 2022) - Kabacińska, Katarzyna; McLeod, Kaleigh; MacKenzie, Annika; Vu, Kim; Cianfrone, Michelle; Tugwell, Andrew; Robillard, Julie M
Objective: The popularity of smartphone technology provides a unique opportunity to make mental health support widely accessible, especially among young people. Despite the promising results of some mobile mental health support applications, the overwhelming number of available applications (apps) on the market makes it difficult to make a choice that will be safe and effective. Currently, widely available tools are either developed by experts, without end user input or are solely based on usability rankings. Thus, it remains unclear what aspects of mental health apps are important for young people. The purpose of this study was to determine what criteria young adults use when they select mental health applications and what is the relative importance of these criteria to inform the development of a user-driven app-rating platform. Methods: We conducted 4 group sessions with 47 youth and young adults aged 15–25 in British Columbia, Canada using a modified nominal group technique. This method allows for establishing the relative importance of criteria in a structured group discussion. We recorded, transcribed and analysed the resulting data using qualitative content analysis and quantitative methods. Results: Criteria that are the most important to young adults when selecting mental health apps include accessibility, security and grounding in scientific evidence. We identified specific aspects of the discussed criteria which were ranked in the order of importance. Conclusion: Consulting end users about their priorities when evaluating mental health apps ensures that their values and priorities are incorporated into future app-rating platforms, alongside expert opinions. The present study also outlines the common contexts in which apps are used as well as their desirable features to inform mental health app development.